Assessing the Perceived Value of Customers for being Satisfied towards the Sustainability of Hypermarket in Malaysia - Polas, Mohammad Rashed Hasan; Hossain, Mohammad Imtiaz; Asheq, Abdul Saboor; Hossain, Nihad; Javed, Md Akib; Nianyu, Li (International Journal of Business, Economics and Management, 2019)
This study examines the relationships between product quality, service quality, pricing strategy and store attributes with customer satisfaction through perceived value using a sample of 211 from 3 hypermarkets in Malaysia. Our results reveal that there are relationships between product quality, service quality and store attributes with perceived value. Furthermore, a positive and significant relationship is also found. However, this study didn’t find any conventional relationship between pricing strategy and perceived value. This study adds to the growing literature of sustainable development of hypermarket. Recently, International marketplace is targeted by so many hooked up outlets, because they’re searching out new capacity marketplace growth. This study focuses on determining the factors that influence on customer satisfaction in the hypermarkets. It is to identify the reasons that impact on customer satisfaction towards hypermarket in Malaysia. In addition, this investigation considers the most noteworthy explanations that improve customer satisfaction towards hyper markets in Malaysia.